Transport of angular momentum in solar-like oscillating stars. Issue Volume 9:Issue S301(2013) (18th February 2014) - Goupil, Mariejo; Deheuvels, Sébastien; Marques, Joao; Lebreton, Yveline; Mosser, Benoit; García, Rafa; Belkacem, Kevin; Mathis, Stéphane
Abstract: Our current understanding and modeling of angular momentum transport in low-mass stars are briefly reviewed. Emphasis is set on single stars slightly younger that the Sun and on subgiants and red giants observed by the space missions CoRoT and Kepler .